NEGARA SEKULARâISLAM Deskripsi Pandangan Dr. Muhammad Syahrur mengenai Hubungan Syura, Demokrasi dan Negara dalam Islam - haris, iir abdul (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2013)
Al-Qur`an as main source of thought in Islam, viewed, has the fundamental norm-ethic and principles of society and individual life needed in the modern democratic state. The State as peak institutional model of human comunity interaction is accumulation of knowledge conscience, ethic value, social and politic behaviour that held in society life as the subjective and objective dimension of state. That can be realizied if civil rights garanted and protected totally as same as everyone can build the human material-spiritual capasities in the diversity paths. Argued, Islam which based to syariah and nubuwwah dimension -- that recited and actuated in contemporary model of syura as high value of islamic democratic and humanity â propose a secular state system based to Islamic fundamental norm.